Acetabular fractures in the elderly population: internal fixation combined with acute total hip arthroplasty - Modesto, Goncalo; Corte-Real, Catarina; Boavida, João; P. Lopes, António (International Journal of Research in Orthopaedics, 2025)
The incidence of acetabular fractures in the elderly population is increasing, primarily due to pre-existing osteoporosis and low-energy trauma. Nevertheless, the optimal treatment algorithm remains a subject of debate. This case report details the treatment of a 77-year-old male patient with an acetabular fracture involving both columns and dome, treated with open reduction and internal fixation plus concomitant total hip arthroplasty.